Análisis del discurso e imagen del expresidente Lenín Moreno, en los mensajes de la presidencia de la república - Calero Jumbo, Stalin Javier (Machala, 2021)
For the public function it is important to maintain a convincing speech that reaches the masses and not only superficially, but that is reflected in them as a construction of their reality, thus, the profile of a candidate or state official is widely accepted at the management level; Similarly, the image becomes a parallel complement to the discourse that makes its function equivalent to the profile of an authority whose social perception is within the parameters that allow governance. For experts in this field of political communication, the control of a communication strategy that is developed under specific parameters such as syntax, rhetoric and stylistics is invaluable, in addition to identifying the functional archetypes to the essence of the candidate and the established social environment, which provide the speaker with an image according to the context and reality in which their management unfolds, for this reason, there is a need to develop work teams that efficiently build a speech that will reach the masses, receiving their attention and later winning approval regarding decision-making about a State. This work analyzes the construction of the speech and image presented by the former president of Ecuador Lenín Moreno Garcés, who repeatedly addressed citizens through the national channel with the program “message from the presidency of the republic”, a space that played relevant issues for the country in the midst of a context surrounded by the Covid-19 pandemic, the state of public corruption and the social outbreak towards its management; supporting the need to know if the management of his speech and image issued were a report developed correctly within his political communication strategy. Within the analysis of this case and due to its interpretive complexity, a mixed approach was approached with preference for qualitative analysis, which allows giving a broader sense to the evaluation of the speech and image developed in the communicational strategies of former president Lenín Moreno Garcés. applied a methodological triangulation based on data collection techniques such as bibliographic review, content analysis, and interviews applied to two professionals with extensive international experience in managing electoral campaigns, preparing speeches and political advice. As a result of this research and once the information was applied and contrasted between the qualitative and mixed methodology with a methodological triangulation, it was possible to establish that the discourse developed by former president Lenín Moreno Garcés is deficient in terms of syntax and style, with a clear lack of rhetoric that manages to persuade citizens, given that, under the context of the COVID-19 pandemic and state of corruption, there was no self-critical speech in its space "message from the presidency of the republic", in addition to the projected image For this reason, it did not obtain a consistent contribution to the discourse, because according to the interviewees and the theoretical foundation it is possible to have a good image, but in politics the handling of a good discourse has more relevance.
Para la función pública es importante el mantener un discurso convincente que llegue a masas y no solo de forma superficial, sino, que quede en ellos plasmado como construcción de su realidad, así, el perfil de un candidato o funcionario estatal queda con una amplia aceptación a nivel de gestión; de igual manera, la imagen se torna un complemento paralelo al discurso que hace que su función sea equivalente al perfil de una autoridad cuya percepción social esté dentro de los parámetros que permiten la gobernabilidad. Para expertos en este campo de la comunicación política, es invaluable el control de una estrategia comunicacional que se desarrolle bajo parámetros específicos como la sintaxis, retórica y estilística, además de identificar los arquetipos funcionales a la esencia del candidato y el entorno social establecidos, que doten al orador de una imagen acorde al contexto y realidad en las que se desenvuelve su gestión, por esto, existe la necesidad de elaborar equipos de trabajos que construyan de forma eficiente un discurso que llegará a masas logrando receptar su atención y posterior ganar la aprobación en cuanto a la toma decisiones sobre un Estado. En este trabajo se analiza la construcción del discurso e imagen presentada por el expresidente de Ecuador Lenín Moreno Garcés, quien se dirigía de forma reiterativa a los ciudadanos mediante cadena nacional con el programa “mensaje de la presidencia de la república”, un espacio que tocaba temáticas relevantes para el país en medio de un contexto envuelto por la pandemia de Covid-19, el estado de corrupción pública y el estallido social hacia su gestión; sustentando la necesidad de conocer si el manejo de su discurso e imagen emitido fueron un aporte desarrollado correctamente dentro de su estrategia de comunicación política. Dentro del análisis de este caso y por su complejidad interpretativa se abordó un enfoque mixto con preferencia de análisis cualitativo, lo que permite dar un sentido más amplio hacia la evaluación del discurso e imagen desarrolladas en las estrategias comunicacionales del expresidente Lenín Moreno Garcés, también se aplicó una triangulación metodológica basada en las técnicas para la recolección de datos como la revisión bibliográfica, análisis de contenido y entrevistas aplicadas a dos profesionales con una amplia trayectoria internacional en el manejo de campañas electorales, elaboración de discursos y asesorías políticas. Como resultado de esta investigación y una vez aplicado y contrastado la información entre la metodología cualitativa y mixta con una triangulación metodológica, se pudo establecer que el discurso desarrollado por el expresidente Lenín Moreno Garcés, es deficiente en cuanto a sintaxis y estilística , con una clara falta de retórica que logre persuadir a los ciudadanos, dado que, bajo el contexto de pandemia por COVID-19 y estado de corrupción , no existió un discurso autocrítico en su espacio “mensaje de la presidencia de la república”, además que la imagen proyectada por el mismo no obtuvo un aporte consecuente al discurso, debido a que según los entrevistados y la fundamentación teórica se puede tener una buena imagen, pero en política el manejo de un buen discurso tiene más relevancia.
Keywords: DISCURSO; IMAGEN; LENIN MORENO; COMUNICACION POLITICA; ESTRATEGIA